Макрофитобентос черноморского побережья Керченского полуострова (Крым, Украина) - Садогурский, С.Е. (Альгология, 2007)
За результатами досліджень 2004 р. наводяться дані про просторовий розподіл, якісний і кількісний склад макрофітобентосу біля м. Ак-Бурун (Крим: пріоритетна ділянка Такил; Чорне море). Охарактеризовано зміни значень показників уздовж берега і з глибиною. Загалом зареєстровано 68 видів макроводоростей: Chlorophyta - 13 (19%), Phaeophyta - 19 (28%), Rhodophyta - 42 (62%). Біомаса бентосної рослинності сягає 0,7-1 кг/м² у псевдоліторалі (32 види водоростей) і 1,5-7 кг/м² у субліторалі (64 види водоростей). Показана доцільність виділення в межах псевдоліторальної зони двох підзон. Альгофлора має виражений олігосапробний характер. За кількістю видів переважають коротковегетуючі водорості, а за біомасою - багаторічні. Акваторію рекомендовано включити до складу ПЗФ. According the results of investigations (2004 year) datas about spatial distribution, qualitive and quantitive staff of macrophytobenthos at the cape Ak-Burun (Crimea: priority district Takyl; Black Sea) are given. Exponents meaning variation along the shore and according to the depth are characterized). It was registrated 68 species macroalgae in whole: Chlorophyta - 13 (19%), Phaeophyta - 19 (28%), Rhodophyta - 42 (62%). Biomass of benthos vegetation is 0,7-1 kg/m² in pseudolittoral (32 species of macroalgae are found) and 1,5-7 kg/m² in sublittoral (64 species of macroalgae are found). Expediency of two subzones allotion in the borders of pseudolittoral zone is shown. Algoflora has high expressed oligosaprobic character. According to the number of species of algaes with short period of vegetation predominate, according to the biomass - perennial species of algaes predominate. Aquatories is recommended to be included to the staff of Nature Reserve Fund.